Effect of Copper on the Corrosion Resistance of Super Austenitic StainlessSteel in Flue Gas Desulfurization Environment - LI Bing-bing, CHEN Hai-tao, LANG Yu-ping, QU Hua-peng, FENG Han-qiu, TIAN Zhi-ling, CHEN Qing-ming (Cailiao Baohu, 2021)
In order to study the effect of Cu on the origin and propagation of pitting corrosion of super austenitic stainless steel, the immersion test results showed that Cu reduced the pitting temperature of super austenitic stainless steel and promoted the nucleation of corrosive pitting. With the analysis of the number of pitting pits, average pitting rate, maximum pitting depth and maximum surface area, it was found that the propagation of pitting was inhibited when Cu content was less than 1%(mass fraction, the same below), and the propagation of pitting was quickened when Cu content was more than 1%. Moreover, the electrochemical potentiostatic polarization curve revealed that Cu had some influence on the corrosion current density, and the EIS and XPS showed that the passivation effect was the optimal when Cu content was 1%.